Oz Virus Infection in 6 Animal Species, Including Macaques, Bears, and Companion Animals, Japan - Matsuu, Aya; Tatemoto, Kango; Ishijima, Keita; Nishino, Ayano; Inoue, Yusuke; Park, Eunsil; Tamatani, Hiroo; Seto, Junji; Higashi, Hideo; Fukui, Yuichi; Noma, Takashi; Doi, Kandai; et al. (Emerging infectious diseases, 2025)
Oz virus (OZV) was isolated from an Amblyomma tick in Japan and shown to cause lethal viral myocarditis in humans. However, the natural reservoirs and the distribution of OZV remain unknown. We describe epidemiologic studies conducted by using serum samples collected from mammals throughout Japan. The results showed that 27.5% of wild boars, 56.1% of Sika deer, 19.6% of Japanese macaques, and 51.0% of Asian black bears were positive for virus-neutralizing antibodies against OZV. Approximately 2.8% of dogs and 1.0% of cats also were seropositive. OZV RNA was not detected in any of the examined animal serum samples. Most seropositive animals were distributed in central and western Japan. OZV infects a wide range of animal species, including companion animals and nonhuman primates, and is distributed through central and western Japan, suggesting that further countermeasures are required to prevent this tickborne zoonotic infection.